2017
DOI: 10.1152/japplphysiol.00023.2017
|View full text |Cite
|
Sign up to set email alerts
|

Muscle hypertrophy in prediabetic men after 16 wk of resistance training

Abstract: Resistance training of healthy young men typically results in muscle hypertrophy and a shift in vastus lateralis composition away from type IIx fibers to an increase in IIa fiber content. Our previous studies of 8 wk of resistance training found that many metabolic syndrome men and women paradoxically increased IIx fibers with a decrease in IIa fibers. To confirm the hypothesis that obese subjects might have muscle remodeling after resistance training very different from healthy lean subjects, we subjected a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…More recently, Stuart et al. () reported that although 16 weeks of resistance exercise training led to an increase in muscle strength and muscle fiber cross‐sectional area within obese, prediabetic men there were no improvements in fasting glucose or insulin concentrations or clamp‐derived measures of insulin sensitivity (so resistance exercise training was only partially effective). Unfortunately, none of these studies included a healthy‐weight control group, so it is not clear if the magnitude of response (i.e., the effectiveness of training) would have been different had the training been undertaken by nonobese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Stuart et al. () reported that although 16 weeks of resistance exercise training led to an increase in muscle strength and muscle fiber cross‐sectional area within obese, prediabetic men there were no improvements in fasting glucose or insulin concentrations or clamp‐derived measures of insulin sensitivity (so resistance exercise training was only partially effective). Unfortunately, none of these studies included a healthy‐weight control group, so it is not clear if the magnitude of response (i.e., the effectiveness of training) would have been different had the training been undertaken by nonobese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Six weeks of one-legged strength training (three times per week) in aged, non-obese, type 2 diabetics increased skeletal muscle GLUT4 in the exercised leg (~40%), but not in healthy controls [93]. In support of these findings, 16 weeks of resistance training increased skeletal muscle GLUT4 protein content in middle-aged (30–54 years) prediabetic, obese men [95] and increased the hypomethylation (promotes gene transcription) of the GLUT4 promoter in middle-aged morbidly obese Maori and Pacific Islanders diagnosed with type 2 diabetes [96]. In contrast to these findings, no changes in skeletal muscle GLUT4 were observed in healthy, non-obese, aged individuals in response to 6 weeks of one-legged strength training [93] or 12 weeks of whole body resistance training [2].…”
Section: Resistance Training and Skeletal Muscle Insulin Signalingmentioning
confidence: 97%
“…However, difficult they are to identify, a certain number of studies have postulated a divergence between SM hypertrophy per se , and intrinsic changes in SM IS or have pointed out a lack of clarity around the mechanisms involved ( Holten et al, 2004 ; Bird and Hawley, 2017 ; Pesta et al, 2017 ). Furthermore, the relationship between relative or absolute FFM and glucose homeostasis is inconsistent across studies ( Gippini et al, 2002 ; Goulet et al, 2007 ; Glouzon et al, 2015 ; Perreault et al, 2016 ; Stuart et al, 2017 ). Amongst these studies, Brochu et al (2008) have shown in non-diabetic postmenopausal women matched for fat mass that those displaying a larger FFM had higher fasting insulin and glucose compared to those with lower FFM ( Brochu et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%